Influence of the use of french oak chip on the physical-chemical and colorimetric composition of red wine from the cultivar Syrah (Research, Society and Development, 2020)
The São Francisco Valley Sub-Middle Region (SFVS) is the second largest wine producing region made with the cultivars Vitis vinífera L. in the country, in which the Syrah variety stands out as the most used in the region for production red wines. Wines made with this cultivar have a high ripening capacity. For this purpose, the effect of using medium toasting French oak chips on the physical-chemical and colorimetric composition of 'Syrah' red wine made at the SFVS was evaluated. Two treatments were tested, one control (without using oak chips) and the other using a medium toasting french oak chips (6 g L-1). The parameters evaluated were: pH, total and volatile acidity, reducing sugars, density, free and total sulfur dioxide, alcoholic content, dry extract, total polyphenols index (TPI), color intensity, hue, and colorimetric analysis using the CIELabe CIEL*C*h system. The results showed that the use of french oak chips can contribute to greater microbiological stability and color of the wines due to the lower pH value found. It was evidenced that the use of oak chips significantly influenced the parameters inherent in the color, obtaining a higher total polyphenols index in wine using the french oak chips.